Design of The 200 MW(t) Pb-Bi Cooled Nuclear Fast Reactor For Steam Membrane Reforming Hydrogen Production - Epung Saepul Bahrum; Zaki Su’ud; Abdul Waris; Bambang Ari Wahjoedi (Indonesian Journal of Physics, 2006)
Design study of the 200 MW(t) Pb-Bi cooled nuclear fast reactor for steam membrane reforming hydrogen production has been proposed. The design base on neutronic, steady state thermalhydraulic and safety examination of the 200 MWt Pb-Bi cooled fast nuclear reactor. For balance cylindrical core demonstrated that at flowrate 7000 kg s-1 and inlet coolant temperature of 350 0C yield average and maximum coolant outlet temperature of 552 and 621 0C. The safety analysis confirm at that situation the coolant and fuel cladding maximum temperature lower than coolant boiling and cladding melting temperature. The 552 0C average coolant outlet temperature corresponds to maximum reaction temperature of the steam membrane reforming which is close to 550 0C. We proposed design of the 200 MW(t) Pb-Bi cooled balance cylindrical core nuclear fast reactor for steam membrane reforming hydrogen production. The configuration of the design is Pb-Bi cooled nuclear fast reactor and steam membrane hydrogen production unit coupled with intermediate heat exchanger. One of the intermediate heat exchanger functions is to protect nuclear reactor when an explosion accident occur in the hydrogen production unit.